Family assessment instrument based on the Nanda taxonomy II domains model (2023)
Introduction: A family is healthy when a balance among the control, growth, stability and spirituality of each of its members is achieved with the surrounding environment (2). Objective: To design a validated instrument that permits family assessment based on the North American Nursing Diagnosis Association (NANDA) Taxonomy II domains model. Methodology: A quantitative design, of the psychometric technological type with descriptive data analysis. The sample for the validation of the instrument comprised eight nursing professionals. In addition, a pilot test was conducted; 40 families from the cities of Bucaramanga and Santa Marta, Colombia, including 20 from each city, participated. For the content validation, the Modified Lawshe's Model was considered. Results: There was a general consensus among the evaluating judges regarding the validation of the content of the instrument. Cronbach's alpha was 0.847. Regarding Spearman's rho nonparametric correlation, there was a good correlation among the items considered by the instrument, with a value of r greater than 0.5, a significance level of <0.05 and a p-value of zero. Conclusions: A bibliographical review was performed, according to the context of family. The Family Assessment Instrument, based on the NANDA Taxonomy II Domains Model and consisting of 45 items, was designed. Consensus among the evaluating judges, a reliability by means of Cronbach's alpha value greater than 0.7 and significant Spearman's rho nonparametric correlations among some items of the instrument were found.